2009
DOI: 10.1074/jbc.m806952200
|View full text |Cite
|
Sign up to set email alerts
|

Phosphonocarboxylates Inhibit the Second Geranylgeranyl Addition by Rab Geranylgeranyl Transferase

Abstract: Rab geranylgeranyl transferase (RGGT) catalyzes the posttranslational geranylgeranyl (GG) modification of (usually) two C-terminal cysteines in Rab GTPases. Here we studied the mechanism of the Rab geranylgeranylation reaction by bisphosphonate analogs in which one phosphonate group is replaced by a carboxylate (phosphonocarboxylate, PC). The phosphonocarboxylates used were 3-PEHPC, which was previously reported, and 2-hydroxy-3-imidazo[1,2-a]pyridin-3-yl-2-phosphonopropionic acid ((؉)-3-IPEHPC), a >25-fold mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
45
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(46 citation statements)
references
References 27 publications
1
45
0
Order By: Relevance
“…We transfected HGC-MIST1 cells with PGC-RFP in the presence of 5 mM 3-PEHPC (3,10), an inhibitor of RAB geranylgeranyl transferase (RGGT), the enzyme that catalyzes the addition of geranylgeranyl groups to the carboxy-terminal dicysteine (CC or CXC) motifs in RAB3D and RAB26 (55). We used the minimal concentration of 3-PEHPC that completely dispersed the normal cellular localization of an eGFP-RAB26 construct.…”
Section: Expression Of Pepsinogen-rfp In Mist1-expressing Stable Linementioning
confidence: 99%
“…We transfected HGC-MIST1 cells with PGC-RFP in the presence of 5 mM 3-PEHPC (3,10), an inhibitor of RAB geranylgeranyl transferase (RGGT), the enzyme that catalyzes the addition of geranylgeranyl groups to the carboxy-terminal dicysteine (CC or CXC) motifs in RAB3D and RAB26 (55). We used the minimal concentration of 3-PEHPC that completely dispersed the normal cellular localization of an eGFP-RAB26 construct.…”
Section: Expression Of Pepsinogen-rfp In Mist1-expressing Stable Linementioning
confidence: 99%
“…72 Substitution of the pyridine ring structure in 3-PEHPC with a imidazo[1,2-a]pyridine cyclic moiety led to the most potent inhibitor of RabGGTase in this compound class, with an IC 50 value of 1.3 μM, nearly 25-fold better than the initial inhibitor structure. 73 It was recently discovered that this class of inhibitors inhibits only the second geranylgeranylation step of RabGGTase, not the first, and it was suggested that the phosphonocarboxylate inhibitors bind in a site adjacent to the active site, preventing the mono-geranylgeranylated protein from translocating to provide room for the second prenylation step to occur. 73 Some Rab proteins are only mono-geranylgeranylated and as a consequence are not inhibited by the phosphonocarboxylates; the development of specific inhibitors of all Rab protein geranylgeranylation has become a high priority.…”
Section: Prenyltransferase Inhibitor Developmentmentioning
confidence: 99%
“…73 Additionally, the (+)-enantiomer of 3-IPEHPC has been found to be more potent than the (−)-enantiomer; however, the more active absolute configuration for the remaining bisphosphonates has yet to be determined. 73 …”
Section: Figurementioning
confidence: 99%
“…16 In contrast the phosphono carboxylate 4 , also known as IPEHPC and viewed as an analogue of the bisphosphonate minodronate ( 5 ), 12,17 shows significantly greater potency even as the racemate, and the (+)-enantiomer 4 is ~60-fold more active than the (−)-enantiomer. 15 However, the (+)-enantiomer also shows weak inhibition of at least one other enzyme involved in isoprenoid biosynthesis, probably geranylgeranyl diphosphate synthase (GGDPS). 16 …”
mentioning
confidence: 99%